A dynamic model of optimal lime application for wheat production in Australia. (9th February 2021) - Shoghi Kalkhoran, Sanaz; Pannell, David; Polyakov, Maksym; White, Ben; Chalak Haghighi, Morteza; William Mugera, Amin; Farre, Imma
Abstract : Soil acidification due to crop removal and the use of acidifying fertilisers reduce land productivity in many agricultural systems worldwide. The most common remedy is to apply lime to the soil surface. An alternative approach is to incorporate lime into the sub‐soil. This is a more expensive option, but it substantially reduces the time required to reduce acidity in the sub‐soil horizons. This paper presents a dynamic optimisation model to determine optimal rates, frequency and methods of lime application for a wheat monoculture system in the northern part of the Western Australian wheatbelt. Results show that optimal application rates depend on rainfall levels and soil‐acidity conditions. The net present value of profit is not sensitive to the frequency of lime application. Incorporating lime into the sub‐soil increases the net present value of profit, but only by a small amount: two to four per cent in most scenarios modelled. In the process, sub‐soil lime application reduces both the optimal lime application rate and the time required for the soil pH to increase to a target level.